Industrial cluster as business strategy to improve rural economy in Malaysia - Yohan Kurniawan; Wan Mohamad Wan Abdullah (2012)
South East Asia has played a major role in the world-economy now, and The ASEAN states have become a major focus for international capitalism, with a population of over 300 millions and some of the higher per capita incomes in the Third World, they have market potential; possibilities for investment given low labour costs and comparative political stability; strategic position between the Indian and Pacific oceans; and the 'openness' of the economies to trade, foreign investment and the activities of multinational corporations. However, the welfare of the community in Southeast Asia is still not over and the poverty rate is still relatively high. One way this is applied at the time of industrial clusters in small and medium enterprises in the village. Small and medium enterprises in the village have a great opportunity to be promoted, but this time the company in this village received less attention and they are not serious in handling the various parties involved. An industry cluster is different from the classic definition of industry sectors because it represents the entire value chain of a broadly defined industry from suppliers to end products, including supporting services and specialized infrastructure. Cluster industries are geographically concentrated and inter-connected by the flow of goods and services, which is stronger than the flow linking them to the rest of the economy. Clusters include both high and low-value added employment. The purpose of this paper is to explain and analyse apllied industrial clusters in the Tumpat rural community, Kelantan, Malaysia. The Industries involved in this project are the traditional cake and industrial catfish industries. There were 17 participants joining this programme and working together with rural industry. The concept of industrial clusters in this project is developing industries related with developing primary industries, which are aimed at supporting the industry to advance the economy in the community. The industrial clusters created for catfish industry are pellet industry, catfish crackers industry, catfish breeder, etc. From the traditional cake industry, the industrial clusters created are pineapple jam industry, printing industry, peanut farming, cake industry hub, etc. If the main business and their industrial clusters grow, the community welfare is also increased. The limitations of the industrial clusters project are financial problem (lack capital business), entrepreneur motivation, lack of interest among the rural community, lack of strategic management, marketing, and finance management knowledge and also lack of networking.